Barriers and facilitators to the implementation of person‐centred care in different healthcare contexts - Moore, Lucy; Britten, Nicky; Lydahl, Doris; Naldemirci, Öncel; Elam, Mark; Wolf, Axel (Scandinavian journal of caring sciences, 2017)
Background To empower patients and improve the quality of care, policy‐makers increasingly adopt systems to enhance person‐centred care. Although models of person‐centredness and patient‐centredness vary, respecting the needs and preferences of individuals receiving care is paramount. In Sweden, as in other countries, healthcare providers seek to improve person‐centred principles and address gaps in practice. Consequently, researchers at the University of Gothenburg Centre for Person‐Centred Care are currently delivering person‐centred interventions employing a framework that incorporates three routines. These include eliciting the patient's narrative, agreeing a partnership with shared goals between patient and professional, and safeguarding this through documentation. Aim To explore the barriers and facilitators to the delivery of person‐centred care interventions, in different contexts. Method Qualitative interviews were conducted with a purposeful sample of 18 researchers from seven research studies across contrasting healthcare settings. Interviews were transcribed, translated and thematically analysed, adopting some basic features of grounded theory. Ethical issues The ethical code of conduct was followed and conformed to the ethical guidelines adopted by the Swedish Research Council. Results Barriers to the implementation of person‐centred care covered three themes: traditional practices and structures; sceptical, stereotypical attitudes from professionals; and factors related to the development of person‐centred interventions. Facilitators included organisational factors, leadership and training and an enabling attitude and approach by professionals. Trained project managers, patients taking an active role in research and adaptive strategies by researchers all helped person‐centred care delivery. Conclusion At the University of Gothenburg, a model of person‐centred care is being initiated and integrated into practice through research. Knowledgeable, well‐trained professionals facilitate the routines of narrative elicitation and partnership. Strong leadership and adaptive strategies are important for overcoming existing practices, routines and methods of documentation. This study provides guidance for practitioners when delivering and adapting person‐centred care in different contexts.